How Healthy Aging and Contact With Children Are Associated With Satisfaction in Middle-Aged and Older Parents in China: A Mediation Analysis - Chen, Jiangyun; Zeng, Yixin; He, Wenjun; Yang, Jiao; Xu, Dong; Li, Haomiao (Frontiers in Public Health, 2022)
Objectives This study aims to examine the mediation role of satisfaction with children on the association between contact with children (CCT) and healthy aging among middle-aged and older parents in China. Methods Data from 9,575 parents over 45 years old were obtained from the 2018 China Health and Retirement Longitudinal Survey. A multinomial logistic regression model was applied to measure the association between contact, satisfaction, and healthy aging with potential confounders controlled. We used the Sobel–Goodman Mediation test to analyze the mediation role of satisfaction on the association between types of CCT and healthy aging. Results Parents with contact with adult children had higher satisfaction with children [for contact weekly (satisfied/unsatisfied): relative risk ratio (RRR) = 2.44, CI = 1.92–3.10] and higher healthy aging [for contact weekly (Q5/Q1): RRR = 1.41, CI = 1.13–1.77]. Satisfaction was strongly related to healthy aging [for satisfied (Q5/Q1): RRR = 3.44, CI = 2.14–5.51], and mediated 19.05% of healthy aging for weekly contact (Sobel test z = 4.338; indirect role = 0.014, CI = 0.011–0.018; direct role = 0.061, CI = 0.029–0.094). Subgroup analysis further revealed that satisfaction with contact played a partial mediating role between monthly contact and healthy aging in female and rural groups. Conclusions Monthly CCT is more appropriate for older parents. Satisfaction with children in older parents seems to act as a significant and partial mediator of the relationship between contact and healthy aging. The contribution of satisfaction to healthy aging could be important to be considered and promoted in women and rural older parents, independent of CCT.